Employee Readiness in Implementing the Core Values of the Indonesian Government Organization “BerAKHLAK” - Siti Rachmawati, Tisa; Sukmawati, Anggraini; Nurhayati, Popong (JDM (Jurnal Dinamika Manajemen), 2024)
This research aims to identify employee perceptions of employee readiness to implement the core values of BerAKHLAK, analyze the influence of leadership, organizational support, and commitment to the organization on employee readiness to change, and formulate policy recommendations to increase employee readiness to change. The survey samples chosen to be the subjects of this research were TNI, POLRI, and ASN, who had active work periods of more than one year. Data processing and analysis were performed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The research results show that the respondents in this study were dominated by employees aged 46-55 years. Based on the results of Structural Equation Modeling data processing, leadership variables and organizational support directly influence employee readiness to change. However, a commitment to the organization has little effect on employee readiness to change. Managerial implications can be implemented by the Secretariat General of the National Resilience Council by implementing the POLC (Planning, Organizing, Leading, Controlling) model. In addition, further research is likely to include other factors related to employee readiness to change.